Transformasi Kaidah Fiqih : Menjawab Kebutuhan Maslahat di Era Media Sosial dan E-Commerce - Andi Tenri Wale; Nur Ramadhani; Kurniati Kurniati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The transformation of fiqh principles is crucial in addressing the challenges of Islamic law in the era of social media and e-commerce. As technology advances, new phenomena such as digital transactions, online communication, and social media interactions significantly influence the social and economic dynamics of the Muslim community. In this context, fiqh principles need to be adjusted to remain relevant to the needs of maslahat (public interest) in contemporary times. This article aims to analyze how fiqh principles can be applied in the context of social media and e-commerce, and how they adapt to the changing times to ensure that Islamic principles continue to safeguard the welfare of the community. The approach used is a literature review, focusing on the adaptation of fiqh in facing digital technological advancements.